Технологии соединения стекла и металла в объектах дизайна; Дизайн. Теория и практика; Вып. 18 - Кухта М. С. Мария Сергеевна; Казьмина О. В. Ольга Викторовна; Соколов А. П. Александр Петрович; Пелевин Е. А. Евгений Александрович (2014, 2014)
Заглавие с экрана